Gestión turística municipal y la conservación del patrimonio histórico/cultural en la ciudad de Iquitos, 2020 - Garcia Macedo, Marleni; Garate Paredes, Xiomara Sofia (Universidad Nacional de la Amazonía Peruana, 2021)
The present study aimed to establish the relationship between municipal tourism management and the conservation of historical / cultural heritage in the city of Iquitos, 2020; because this study belonged to an applied research type and descriptive-correlational level accompanied by a non-experimental design, being the sample of 369 residents of the city of Iquitos, who were asked by means of a questionnaire of questions respectively; obtained as results municipal tourism management has presented certain deficiencies, since municipal regulations and provisions sometimes facilitate the entry, movement and return of tourists, activities are rarely carried out to promote tourism products and services and training is rarely offered, without However, the municipality does not always promote tourist recreation for the population. On the other hand, the conservation of the historical / cultural heritage is regular; since sometimes defense strategies and / or management plans are implemented for the identified heritage sites, but if they are kept in optimal conditions, likewise, the municipality has rarely imposed norms for the conservation of heritage and tourist circuits sometimes include destinations cultural and historical. It was concluded that there is a significant relationship between municipal tourism management and the conservation of historical / cultural heritage; relation of 0.647 ** which is positive mean.

El presente estudio tuvo como objetivo establecer la relación entre la gestión turística municipal y la conservación del patrimonio histórico/cultural en la ciudad de Iquitos, 2020; pues dicho estudio perteneció a una investigación de tipo aplicada y de nivel descriptiva-correlacional acompañado de un diseño no experimental, siendo la muestra de 369 pobladores de la ciudad de Iquitos, a quienes se les encuestó mediante un cuestionario de preguntas respectivamente; obteniendo como resultados que la gestión turística municipal ha presentado ciertas deficiencias, pues las normativas y disposiciones municipales a veces facilitan el ingreso, desplazamiento y retorno de los turistas, pocas veces se realizan actividades para promocionar los productos y servicios turísticos y pocas veces se ofrecen capacitaciones, sin embargo, la municipalidad no siempre promueve la recreación turística de la población. Por otro lado, la conservación del patrimonio histórico/cultural es regular; pues a veces se implementan estrategias de defensa y/o planes de manejos para los sitios patrimoniales identificados, pero si se mantienen en óptimas condiciones, asimismo, la municipalidad raras veces han impuesto normas para la conservación del patrimonio y los circuitos turísticos a veces incluyen destinos culturales e históricos. Se concluyó que existe una relación significativa entre la gestión turística municipal y la conservación del patrimonio histórico/cultural; relación de 0,647** la cual es positiva media.
Keywords: Turismo; Gestión; Conservación de los bienes culturales; Municipalidad; https://purl.org/pe-repo/ocde/ford#5.06.02